2017
DOI: 10.1038/s41598-017-08248-8
|View full text |Cite
|
Sign up to set email alerts
|

Bpifcl modulates kiss2 expression under the influence of 11-ketotestosterone in female zebrafish

Abstract: The bactericidal/permeability-increasing (BPI) fold-containing (BPIF) superfamily of genes expressed in the brain are purportedly involved in modulating brain function in response to stress, such as inflammation. Kisspeptin, encoded by kiss, is affected by inflammation in the brain; therefore, BPIF family genes might be involved in the modulation of kisspeptin in the brain. In this study, we investigated the expression of BPIF family C, like (bpifcl) in zebrafish brain and its involvement in kiss2 regulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…gonads of female and male-like female) in T. okinawae (electronic supplementary material, table S9). A previous study using Zebrafish revealed that this gene modulates the expression of kiss2 , an orthologous gene regulating reproductive development through GnRH neuronal activity in mammals [37]. Interestingly, kisspeptin may have other neuroendocrinal functions on social and sexual behaviour by regulating neurons that express isotocin and vasotocin, although it is not a direct regulator of reproduction through GnRH neurons in several fish species [3840].…”
Section: Discussionmentioning
confidence: 99%
“…gonads of female and male-like female) in T. okinawae (electronic supplementary material, table S9). A previous study using Zebrafish revealed that this gene modulates the expression of kiss2 , an orthologous gene regulating reproductive development through GnRH neuronal activity in mammals [37]. Interestingly, kisspeptin may have other neuroendocrinal functions on social and sexual behaviour by regulating neurons that express isotocin and vasotocin, although it is not a direct regulator of reproduction through GnRH neurons in several fish species [3840].…”
Section: Discussionmentioning
confidence: 99%
“…BPIFC protein is mainly expressed in human epidermis (Toulza et al, ) and highly expressed in the basal layer of the epidermis from inflammatory skin of patients with psoriasis (Mulero et al, ). In zebrafish, BPIF family C, like ( bpifcl ) modulates the expression of Kisspeptin that a molecule known to be affected by inflammation in the brain (Moriya, Tahsin, & Parhar, ). Comparison of the mouse and human orthologs showed that BPIFC protein is evolving rapidly, having an elevated Ka/Ks ratio similar to the PLUNC protein family and BPI protein (Bingle et al, ), which implies that BPIFC protein is involved in host defense.…”
Section: Discussionmentioning
confidence: 99%